A Discrete Sensitivity Solver for an Industrial CFD Code via Automatic Differentiation. - Standingford, David W. F.; Forth, Shaun A. (Cranfield University, 2002)
We report on development and validation of a discrete sensitivity solver for the BAE SYSTEMS/Airbus UK CFD code FLITE-3D. We used the Odyssee automatic differentiation (AD) tool to create a discrete forward sensitivity version of FLITE-3D. Validation is via comparing sensitivities of integrated forces (lift, drag, side force) with respect to (w.r.t) angle-of-attack (AoA) , calculated using the sensitivity solver and central-differencing. Validation, w.r.t. changes in the surface and field mesh, is performed by setting sensitivities of all mesh related quantities as if rotated by an infinitesimal angle D alpha. Such sensitivities correspond to those calculated w.r.t AoA alpha. We investigate calculating discrete sensitivities under 2 approximations regarding so-called mesh sensitivities, concluding that they are not applicable to FLITE- 3D. We present results of a wing geometry optimisation using forward sensitivities.